CONCEPTS OF MARKETING STRATEGIES FOR ENSURING COMPETITIVENESS IN ENTERPRISES - Mullabayev Baxtiyarjon Bulturbayevich; Rаvshаnbеkоv Оybеk Rustambek o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article presents the concepts of marketing strategies for ensuring competitiveness in enterprises, the methodological approach aimed at increasing the competitiveness of light industry enterprises based on marketing strategies, and the improvement and simplification of the cluster method based on mutual relations. The article presents ideas and comments on the method of assessing the competitiveness of industrial enterprises, the enterprise’s integral indicators (efficiency of production, marketing, financial, management, logistics and innovation activities) and its adaptation to the market environment.